A relação escola e família: desafios e possibilidades para uma construção participativa - Sobral, Alexandra Alves (2023)
This research explores the relationship between school and family from the perspective of democratic administration, with the general objective of collectively developing strategies to promote family participation in school administration processes. The research took place at the Municipal School of Early Childhood Education (EMEI), located in the far East Zone of São Paulo, in the neighborhood of Cidade Tiradentes, with families of the children enrolled in this educational unit. The qualitative research utilized a methodological procedure of five formative meetings, inspired by the assumptions of action research, with families of the students, using generative themes as triggers for reflective work and dialogue construction among participants, looking at the reality of the territory and the daily life lived by these families, in the pursuit of promoting active participation and considering the voices of families in decision-making instances, as well as reflecting on the current challenges for the expansion and qualification of this relationship, in the possibility of creating a space of community welcome and strengthening. The theoretical foundation was based the concepts of Democratic Administration, Dialogicity, Awareness, and the Relationship between Family and School were anchored in the theorists Vitor Paro (1998), Paulo Freire (2013), (2017), and Heloisa Szymanski (2001). Data analysis was carried out in the light of Prosa Analysis by André (1983). By relying on the assumptions of action research, it was possible to perceive the engagement of participants in critical reflection on the reality in which they are inserted, collectively reflecting on the resolution of problems raised by the group. Throughout this process, participants built individual and collective knowledge, new skills and attitudes that will enable the re-signification of values and the transformation of undesirable situations. The interaction and exchange of knowledge favored the strengthening of participants as social subjects and led to awareness-raising, as the representations of these subjects are recognized or transformed when they interact with the researcher and other people who experience similar situations. During this research, it was possible to observe how the school institution is still rooted in vertical postures, revealing a great challenge in building a space of empathy among peers and families. Through the analysis of the collected data, the difficulty of professionals in the school unit to act democratically was also verified. This points to the need for training the entire school community, as well as working on interpersonal relationships within this space. Based on these researched elements, our intention was to broaden this reflection and demonstrate the importance of effective participatory practice in the process of social transformation and Brazilian public schools